Modelling and simulation of solar photovoltaic systems with maximum power tracking algorithms - Lum, Joanna Jia Min (Nanyang Technological University, 2024)
This project presents the modelling and simulation of Solar Photovoltaic (PV) systems employing an enhanced Perturb-and-Observe (P&O) Maximum Power Point Tracking (MPPT) algorithm. The P&O algorithm is widely adopted due to its simplicity; however, it exhibits limitations in rapidly adapting to dynamic environmental conditions such as fluctuating solar irradiance and temperature. Additionally, under partial shading conditions, the conventional P&O algorithm often converges to the second peak, failing to identify the global maximum power point (MPP). This work improves upon the standard P&O algorithm by incorporating a method that accounts for the extent and severity of shading across the PV panels, enabling the accurate detection of the global MPP under partial shading. All simulations are conducted using PLECS, with the PV system modelled as a two-series, two-parallel array interfaced with a DC/DC converter. The proposed MPPT algorithm demonstrates an improved capacity to accurately track the global MPP under varying shading conditions.